Graphene Materials Advanced Applications - Kyzas, George Z.; Mitropoulos, Athanasios Ch (IntechOpen, 2017)
Graphene is, basically, a single atomic layer of graphite, an abundant mineral that is an allotrope of carbon that is made up of very tightly bonded carbon atoms organized into a hexagonal lattice. What makes graphene so special is its sp2 hybridization and very thin atomic thickness (of 0.345 Nm). These properties are what enable graphene to break so many records in terms of strength, electricity, and heat conduction (as well as many others). This book gathers valuable information about many advanced applications of graphene (electrical, optical, environmental, cells, capacitors, etc).